AN ANALYSIS OF ARABIC WRITING SKILL LEARNING DIFFICULTIES AMONG SECONDARY SCHOOL STUDENTS | تحليل صعوبات تعلم مهارة الكتابة باللغة العربية لدى طلاب المرحلة الثانوية - Muhammad Arif Nasruddin; Silvia Fauziyah (Universitas Islam Negeri Palopo, 2026)
This study investigates the difficulties encountered by students in learning Arabic writing skills at SMA Islam Kepanjen. The research emphasizes three main aspects, namely the implementation of Arabic writing instruction, the learning difficulties experienced by students, and the teachers’ efforts to overcome these challenges. This study adopted a qualitative case study design. Data were gathered through classroom observations, interviews, and documentation. The findings reveal that the teaching of Arabic writing skills at SMA Islam Kepanjen has been implemented relatively well. However, students still encounter several difficulties, particularly in writing Arabic letters, arranging sentences, applying grammatical rules, and expressing ideas in written Arabic. Students’ low interest and motivation also become significant challenges. To address these difficulties, teachers have undertaken several efforts, such as providing motivation and guidance, conducting additional writing exercises, and allocating extra instructional time. يهدف هذا البحث إلى تحليل صعوبات تعلم مهارة الكتابة باللغة العربية لدى طلاب المدرسة الثانوية الإسلامية كيبانجين. ويركز التحليل على ثلاثة جوانب رئيسية: عملية تعليم مهارة الكتابة، وأنواع الصعوبات التي يواجهها الطلاب، واستراتيجيات المعلمين في معالجتها. استخدم هذا البحث المنهج الكيفي من خلال تصميم دراسة الحالة، وجُمعت البيانات عن طريق الملاحظة، والمقابلات، والوثائق. أظهرت النتائج أن تعليم مهارة الكتابة قد نُفِّذ بصورة جيدة نسبياً، بيد أن الطلاب لا يزالون يواجهون صعوبات خاصة في كتابة الحروف العربية، وترتيب الجمل، وتطبيق القواعد النحوية، وانخفاض الدافعية. ولمعالجة هذه الصعوبات، بذل المعلمون جهوداً متعددة منها تقديم حصص إضافية، وتنفيذ تدريبات في الكتابة، وتخصيص وقت إضافي لتحسين مهارة الكتابة لدى الطلاب.